2015
DOI: 10.2196/jmir.4818
|View full text |Cite
|
Sign up to set email alerts
|

Empowerment of Cancer Survivors Through Information Technology: An Integrative Review

Abstract: BackgroundPatient empowerment may be an effective approach to strengthen the role of cancer survivors and to reduce the burden on health care. However, it is not well conceptualized, notably in oncology. Furthermore, it is unclear to what extent information technology (IT) services can contribute to empowerment of cancer survivors.ObjectiveWe aim to define the conceptual components of patient empowerment of chronic disease patients, especially cancer survivors, and to explore the contribution of existing and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
95
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(103 citation statements)
references
References 79 publications
(156 reference statements)
3
95
0
5
Order By: Relevance
“…Empowerment is a factor that may be associated with HRQOL and has become a topical issue in cancer survivorship over recent years 5, 6, 7, 8, 9, 10. With its roots in community psychology, empowerment originally was defined as “the mechanism by which people, organizations, and communities gain mastery over their lives.”11 The topical nature and the extensive (mis)use of empowerment in health care has led to a lack of clarity in regard to its definition and measurement 12.…”
Section: Introductionmentioning
confidence: 99%
“…Empowerment is a factor that may be associated with HRQOL and has become a topical issue in cancer survivorship over recent years 5, 6, 7, 8, 9, 10. With its roots in community psychology, empowerment originally was defined as “the mechanism by which people, organizations, and communities gain mastery over their lives.”11 The topical nature and the extensive (mis)use of empowerment in health care has led to a lack of clarity in regard to its definition and measurement 12.…”
Section: Introductionmentioning
confidence: 99%
“…They claimed that all patients should be equipped with a comprehensive treatment summary and follow-up care plan [12]. Further, Groen et al [13] found out that among others educational services including care plan services brought to the patient through IT services may contribute to patient empowerment. They conclude that it is important to consider the needs of a patient when developing IT services, and to create services that are attractive and easy to use.…”
Section: Benefits and Limitations Of The Approachmentioning
confidence: 99%
“…In future work, an automatic data upload from medical devices or gadgets should be implemented to simplify the usage of this feature and to ensure the long-time use of the app as a follow-up care tool. In addition to the information page, additional components for empowerment could be integrated such as patient-to-patient services [2] or patient portal services [13]. For example, the patient could be enabled to record the health status on a weekly or even daily basis and the app could integrate values from smart devices.…”
Section: Benefits and Limitations Of The Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…• Cancer -The empowerment of patients with cancer can contribute to them being autonomous and respected, having knowledge, having psychosocial and behavioural skills, receiving support from community, family, and friends (Groen et al, 2015). In this respect, eHealth applications can support knowledge transmission, including electronic survivorship care plans, and patient-to-patient or patient-tocaregiver communication (Groen et al, 2015).…”
Section: Related Workmentioning
confidence: 99%